Word on the Street: The Persistence of Leftist-dominated Protest in Europe. Issue 2 (3rd March 2016) - Torcal, Mariano; Rodon, Toni; Hierro, María José
Abstract : Classic studies of protest politics have traditionally defended the dominant left-wing orientation of protesters. However, some recent research has highlighted the general spread of protest by the increasing participation of right-wing individuals. Has this process meant an 'ideological normalisation' of protesters? The present article tackles this question by examining competing hypotheses regarding the relationship between ideology and political protest. Through a hierarchical multilevel design, the article tests whether left-wing (or right-wing) supporters are more likely to stay at home when left-wing (right-wing) parties are in power and whether they intensify their protest activities when they are more distant from the government's ideological position. The article shows that left-wing individuals protest more under right-wing governments than under left-wing governments and yet, they are the group which protest the most also under left-wing governments. Both party mobilisation and values appear to be behind these individuals' greater propensity to participate regardless of the governments' ideological orientation.